The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1039/c5cy02111a
|View full text |Cite
|
Sign up to set email alerts
|

Fe/γ-Al2O3and Fe–K/γ-Al2O3as reverse water-gas shift catalysts

Abstract: Fe–K/Al2O3 is shown to be an effective RWGS catalyst with high CO selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 61 publications
(90 reference statements)
9
75
0
Order By: Relevance
“…Table 2 provides preliminary results that support literature findings on the necessity of adding potassium to the catalyst matrix to achieve higher catalyst activity [24,32,33]. Without the addition of potassium to the catalyst matrix, CO 2 conversion drops to 17% and both the methane (35%) and carbon monoxide (11%) selectivities increase (Table 2).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Table 2 provides preliminary results that support literature findings on the necessity of adding potassium to the catalyst matrix to achieve higher catalyst activity [24,32,33]. Without the addition of potassium to the catalyst matrix, CO 2 conversion drops to 17% and both the methane (35%) and carbon monoxide (11%) selectivities increase (Table 2).…”
Section: Resultssupporting
confidence: 76%
“…Table 1 shows that a pure iron catalyst (100Fe/K) has similar activity to what has been previously published for studies performed at 300 °C and 290 psi [6,9,31,32,33]. The overall CO 2 conversion was 24%, 79% of which was converted into useful hydrocarbons.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Kinetic studies showed that, for aF e ÀK/Al 2 O 3 catalyst, ac ombination of redox and associativep athways occurs, with the redox mechanismd ominating. [82] Scheme 2s hows the elementary reactions for each proposed mechanism. In the redox pathway,C O 2 adsorbs and dissociates on the reduced active sites, which leads to the oxidation of actives ites.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…[82] Scheme3.Reduction and carburization steps of an iron-based catalyst. [82] Scheme3.Reduction and carburization steps of an iron-based catalyst.…”
mentioning
confidence: 99%